Psychosocial strain and coping of Finnish working mothers during the COVID-19 lockdown : a job demand-control approach - Panula, Venla (Frontiers Media SA, 2025)
Introduction: In March 2020 many countries around the world, including Finland, implemented lockdown measures to mitigate the unprecedented impacts of the coronavirus infectious disease (COVID-19) on public health. As a result, school and daycare settings closed indefinitely and working from home became the new normal for a big part of the workforce, which came with increased homeschooling and childcare responsibility for mothers.
Methods: In this article we present the findings from maternal responses to open ended questions on psychosocial well-being, and experiences of combining work, family life and homeschooling during the COVID-19 national lockdown in Finland in March–May 2020. Working mothers’ responses (n = 72) were analyzed through the lens of Karasek’s job demand-control model, focusing on how the mothers experienced the demands of their life during the lockdown, and how they saw their possibilities to control the situation.
Results: The findings indicated important variation in the level of experienced demand and control and associated compensatory factors during the COVID-19 lockdown across different subgroups of working mothers.
Discussion: The findings have implications for understanding strain and plausible supports among working mothers during the COVID-19 lockdown as well as in the face of acute adversity including the next possible public health crisis.